Advantages and Current Issues of Blockchain Use in Microgrids - Konashevych, O.I. (Электронное моделирование, 2016)
This paper provides the analysis of the blockchain use in microgrids. The analysis is given from the hypothesis that with the help of IT instruments, self-governed decentralized organizations based on blockchain technology will take and perform public functions traditionally performed by central authorities and corporations in order to organize their relations within the microgrids.